2017
DOI: 10.1007/s12664-016-0726-0
|View full text |Cite
|
Sign up to set email alerts
|

Transduodenal ampullectomy for ampullary tumors

Abstract: Transduodenal ampullectomy (TDA) is indicated for large ampullary tumors, for presence of dysplasia on endoscopic biopsy, for poor surgical candidates for pancreaticoduodenectomy, and in cases not indicated for endoscopic ampullectomy. Retrospective review of data from 2009 to 2015 revealed 11 patients who underwent TDA. Magnetic resonance imaging cholangiopancreatography (MRI-MRCP), contrast-enhanced computed tomography (CECT) scan, side-viewing endoscopy, and endoscopic ultrasound (EUS) were used for investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…After screening of titles and abstracts, 367 studies remained. Finally, 59 papers were eligible to be included into the meta-analysis after full-text evaluation (42 EA, 8 SA, 1 PD, 3 SA + PD, 4 EA + SA, 1 EA + PD; Figure 1 PRISMA chart) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ...…”
Section: Resultsmentioning
confidence: 99%
“…After screening of titles and abstracts, 367 studies remained. Finally, 59 papers were eligible to be included into the meta-analysis after full-text evaluation (42 EA, 8 SA, 1 PD, 3 SA + PD, 4 EA + SA, 1 EA + PD; Figure 1 PRISMA chart) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ...…”
Section: Resultsmentioning
confidence: 99%
“…Currently, although the approach of local tumor resection in the treatment of duodenal papillary tumors is attracting increasing attention from experts and scholars in China and other countries, there is still much debate over its indications and effects. Studies have demonstrated that the indications of local tumor resections include: Benign tumors at the duodenal papilla; pathologically confirmed malignant transformation of benign tumors; tumors with a diameter ≀ 2 cm, no infiltration, a margin with negative biopsy results, and no lymph node metastasis; well differentiated duodenal papillary cancer with a diameter < 1 cm and no lymph node metastasis (T 1-2 N 0 M 0 ); for older patients with multiple complications and higher surgical risks, local tumor resection can be adopted to improve the quality of life[ 3 , 4 ]. Most researchers believe that for benign tumors and early malignant tumors (T 1-2 N 0 M 0 ) in that area, the long-term outcomes of local mass resection are similar to those of pancreaticoduodenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, data of surgical ampullectomies are very few, and included between 11 and 44 patients per case series with an R0rate between 63 and 100% (39,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). Overall complications were between 9 and 68% but 30-day-mortality often was missing.…”
Section: Discussionmentioning
confidence: 99%